2015
DOI: 10.1093/jxb/eru522
|View full text |Cite
|
Sign up to set email alerts
|

Plant membrane assays with cytokinin receptors underpin the unique role of free cytokinin bases as biologically active ligands

Abstract: HighlightCytokinin receptors studied in a novel plant assay system recognize cytokinin ribosides poorly, unlike cytokinin bases. Molecular modelling explained this receptor feature. Some receptors were suggested to function as pH sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
162
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(171 citation statements)
references
References 70 publications
7
162
1
1
Order By: Relevance
“…A significant stomatal closure was observed from 10 nM with an optimal effect at 1 mM. These concentrations are physiologically relevant as AHK3 has a high affinity for t-Z with a K d of 4.3 nM (Lomin et al, 2015). Moreover, we found that, within the CK receptors, only AHK3 participates in t-Zmediated stomatal responses.…”
Section: A Plant Growth-promoting Hormone Induces Stomatal Closurementioning
confidence: 54%
“…A significant stomatal closure was observed from 10 nM with an optimal effect at 1 mM. These concentrations are physiologically relevant as AHK3 has a high affinity for t-Z with a K d of 4.3 nM (Lomin et al, 2015). Moreover, we found that, within the CK receptors, only AHK3 participates in t-Zmediated stomatal responses.…”
Section: A Plant Growth-promoting Hormone Induces Stomatal Closurementioning
confidence: 54%
“…The cytokinin molecule may be inactivated by the removal of the side chain by cytokinin oxidase/dehydrogenase (CKX), or metabolized to storage O-glucosides (which can be released to active forms by b-glucosidases) or 7-and 9-glucosides (which appear not to be reactivated). The free bases are considered the active forms perceived by cytokinin receptors (Lomin et al, 2015) and the ribosides the translocated forms. Cytokinins may also be formed by tRNA-IPTs.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that LCO-induced accumulation of 414iP is more sensitive to negative regulation by ethylene, as compared to accumulation of tZ.415However, the mechanistic basis for this difference is currently unclear. Sensitivity to different 416 cytokinins differs between individual cytokinin receptors(Lomin et al, 2015; Stolz et al, 417 2011). The arabidopsis AtAHK4/AtCRE1 cytokinin receptor possesses similar sensitivity to 418 both iP and tZ(Lomin et al, 2015;Stolz et al, 2011).…”
mentioning
confidence: 99%
“…Sensitivity to different 416 cytokinins differs between individual cytokinin receptors(Lomin et al, 2015; Stolz et al, 417 2011). The arabidopsis AtAHK4/AtCRE1 cytokinin receptor possesses similar sensitivity to 418 both iP and tZ(Lomin et al, 2015;Stolz et al, 2011). AtAHK4/MtCRE1 represents that 419 closest ortholog of MtCRE1 and LjLHK1 and was shown to functionally complement the 420 nodulation defect of the Ljlhk1 mutant(Gonzalez-Rizzo et al, 2006;Held et al, 2014; Op den 421 Camp et al, 2011;Plet et al, 2011).…”
mentioning
confidence: 99%